Strategi Pengembangan UKM Kakaku Coffee dengan Metode Analisis SWOT - Stefani Christin; Akbelhaqqi Dalhats; Kevin Pratama Nafis; Marvellino Kurniawan; Rozak Uyub Faozan; Lindawati Kartika (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The coffee shop industry in Indonesia is experiencing rapid growth, driven by the cultural tradition of coffee consumption and the transformation of digital-based businesses. Kakaku Coffee, founded by Fitra Alhady in 2020 in East Jakarta, is a successful example of a coffee shop that combines high-quality coffee with an authentic Japanese cultural concept. Despite achieving initial success, Kakaku Coffee faces challenges such as long service times and limited parking space. This study aims to formulate a comprehensive development strategy for Kakaku Coffee using SWOT analysis. By identifying the internal and external factors affecting Kakaku Coffee's performance, this study provides practical and applicable recommendations. The method used is descriptive qualitative research with purposive and snowball sampling techniques. The analysis results show five strengths, five weaknesses, four opportunities, and three threats faced by Kakaku Coffee, along with applicable TOWS strategies. This research is expected to serve as a reference for other SMEs looking to adopt similar strategies in a competitive industry.